HUBUNGAN PENGETAHUAN PUS DENGAN KEGAGALAN PEMAKAIAN KONTRASEPSI PIL DI WILAYAH KERJA PUSKESMAS BEBESEN KABUPATEN ACEH TENGAH - Rahma Yani; nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2021)
The vision of the BKKBN in 2020 is to become a reliable and trusted institution in realizing a balanced growing population and quality families. And its mission has five values, namely smart, tough, cooperative, integrity and sincere. The combined oral contraceptive pill, often referred to as the birth control pill or colloquially called the “pill”, is a type of birth control designed to be taken orally by women. It is a combination of estrogen and progesterone. The purpose of this study was to determine the knowledge of couples of childbearing age (EFA) with the failure to use contraceptive pills in the Bebesen Health Center Work Area, Central Aceh Regency. This research is descriptive analytic with cross sectional approach. The sampling technique in this study used random sampling method using the Slovin formula and obtained a sample of 97 acceptors. The results of the study of 97 acceptors experienced failure as many as 84 acceptors (86.8%), which was influenced by the knowledge of family planning acceptors who were in the sufficient category, namely 63 acceptors (64.95%).